Capitalizing on Protecting Groups to Influence Vinyl Catechol Monomer Reactivity and Monomer Gradient in Carbanionic Copolymerization. Issue 12 (29th March 2017) - Leibig, Daniel; Lange, Anna‐Katharina; Birke, Alexandra; Frey, Holger
Abstract : Carbanionic polymerization of vinyl‐catechol monomers with systematically varied acetal protecting groups is studied. In situ 1 H NMR kinetics reveals that protecting groups in direct vicinity to the propagating vinyl moiety can be used to control monomer reactivity and thereby the monomer gradient in copolymers. Abstract : Several vinyl catechol‐based monomers with systematically varied acetal protecting groups suitable for carbanionic polymerization are introduced. All monomers are based on the 4‐vinyl benzodioxole or 5‐vinyl benzodioxole structure and differ in the nature of the protecting group for the catechol functionalities. Different symmetric ketones are used for the protection of the diol functionality. Polymers with average molecular weight from 2500 to 25 000 g mol −1 ( M w / M n < 1.15) are obtained from homopolymerization of the protected monomers. All monomers are examined regarding the influence of the protecting group on the copolymerization behavior with styrene, using in situ 1 H NMR kinetic studies. Length and structure of the alkyl chains generally show no influence for all monomers based on 5‐vinyl benzodioxole. In contrast, all monomers with the protecting group in direct vicinity to the propagating vinyl moiety exhibit dependence between monomer reactivity and chain length of the protecting group. A decrease of the monomer reactivity enables control of the gradient in the copolymerization with styrene. Finally, the first terpolymerization kinetics of a carbanionic polymerization in 1 H NMR kinetics is presented, combining the monomers 3‐vinyl catechol acetonide, styrene, and 4‐vinyl catechol acetonide, which enables the one‐pot synthesis of double gradient terpolymers.